Qualitative Attributes of Contemporary Financial Statements - Błażyńska, Joanna (Studia Oeconomica Posnaniensia, 2015)
Financial reporting is not static in nature: it changes along with the expectations of the users of the information generated by the accounting system. The aim of this paper is to identify the attributes of contemporary financial statements. The article shows the place of financial statements in contemporary business reporting as well as the factors which affect the form of such reports. An analysis of the qualitative attributes of financial statements has been performed on the basis of the Framework for Financial Reporting as well as the findings of scientific research in this field.